A Reply to Mr. Hodas - Monk, David H. (Education Policy Analysis Archives, 1993)
David Monk offers arguments in rebuttal of the article by Steven Hodas (Problems with the Production Function Model in Education) which was published in this journal as Issue 12 of Volume 1.